Austin Independent School District v. United States on Petition for Writ of Certiorari to the United States Court of Appeals for the Fifth Circuit - Supreme Court of the U. S., Washington, DC.; Supreme Court of the U. S., Washington, DC. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1976)
This document presents the Supreme Court decision on the legal suit between the Austin Independent School District and the United States. It is a response to the school system's petition for a writ of certiorari to the United States Court of Appeals for the fifth circuit. The Court of Appeals had ruled that extensive cross-town transportation was to be used in order to achieve racial balance in every school in Austin, Texas. The Supreme Court reviewed the case in light of Washington V. Davis and decided that the Court of Appeals erred by a readiness to impute to the Austin School officials a segregative intent far more pervasive than the evidence justified, and that the Appeals court erred in ordering a desegregation plan that far exceeded any identifiable violations of constitutional rights. The Supreme Court found that the remedy ordered by the Court of Appeals exceeded that which was necessary to eliminate the effect of any official acts of omission on the part of the school system. Justices Brennan and Marshall dissented because they were persuaded that "the Court of Appeals correctly interpreted and applied the relevant decisions of this court". (Author/AM)
ERIC Note: No. 76-200. Decided December 6, 1976 ; Best copy available.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Bus Transportation; Desegregation Litigation; Racial Integration; School Desegregation; Supreme Court Litigation; Texas (Austin); Austin Independent School District TX; Legal/Legislative/Regulatory Materials